TASK SKILL APARATUR SIPIL NEGARA (STUDI KASUS PADA DINAS KEPENDUDUKAN DAN PENCATATATAN SIPIL KABUPATEN SAMPANG, JAWA TIMUR, INDONESIA) - Abdurahman; R.A Ratih Sonia Paradita; Dewi Casmiwati; Wildan Taufik Raharja (Faculty of Social and Political Science, 2021)
The state civil apparatus as the government administrator, service, and development is required to have adaptability in the 4.0 era, especially in organizing population administration service to explore the task skills of the state civil apparatus in the Department of Population and Civil Registration in Sampang, East Java, Indonesia. This study uses descriptive qualitative with interactive model data analysis techniques (Miles, Huberman, and Saldana, 2014: 8). Meanwhile, the theoretical study of task skills Fleishman, et al. (1991) include; knowledge dimension, the apparatus does not master the standard operating procedures that have been set by the Department of Population and Civil Registration; physical agility dimension, most of the apparatus only